Sistem Rekomendasi Masjid Ramah Pemudik Menggunakan Hybrid Rating Aggregation dan Location Based Filtering Berbasis Ulasan Pengguna (Studi Kasus Kabupaten Situbondo) - Rifal Rifqi Rhomadon; Joseph Dedy Irawan; Febriana Santi Wahyuni (JUSIFOR : Jurnal Sistem Informasi dan Informatika, 2025)
The tradition of mudik in Indonesia increases public mobility during the festive season, including in Situbondo Regency. This condition creates a need for information about traveler-friendly mosques that can serve as places of worship as well as rest areas. However, limited information regarding mosque facilities and comfort often makes it difficult for travelers to find suitable locations. This study aims to develop traveler-friendly mosque recommendation system using the Hybrid Rating Aggregation and Location-Based Filtering methods based on user reviews. Sentiment analysis on user reviews was carried out using the Lexicon-Based Sentiment Analysis method to determine the tendency of positive or negative opinions toward each mosque. The result of the sentiment analysis are incorporated into scoring mechanism to improve the accuracy nor suitability of those recommendations. Performance system was performed using blackbox testing approach to verify that each feature performs as expected based on user needs. The results indicate that system operates effectively and is able to deliver mosque recommendations that are informative, reliable, and user-friendly.